The Effects of a Parent-Implemented Language Intervention on Late-Talkers’ Expressive Skills: The Mediational Role of Parental Speech Contingency and Dialogic Reading Abilities - Suttora, Chiara; Zuccarini, Mariagrazia; Aceti, Arianna; Corvaglia, Luigi; Guarini, Annalisa; Sansavini, Alessandra (Frontiers in Psychology, 2021)
Several qualitative and quantitative features of parental speech input support children's language development and may play a critical role in improving such process in late talkers. Parent-implemented interventions targeting late-talkers have been developed to promote children’s language outcomes by enhancing their linguistic environment, i.e., parental speech input. This study investigated the effect of a parent-implemented intervention in increasing late talkers' expressive skills through modifications in structural and functional features of parental speech input. Forty-six thirty-one-month-old late talkers differing in their birth condition (either low-risk preterm or full-term) participated in the study with a parent; 24 parent-child dyads received a parent-implemented intervention centered on dialogic reading and focused stimulation techniques, whereas the other 22 dyads constituted the control group. At pre- and post-intervention, dyads took part in a parent-child shared book-reading session and both parental and child’s speech measures were collected and examined. Results showed that the intervention positively affected parents’ use of responses and expansions of children’s verbal initiatives, as well as the parental amount of talking over reading, whereas no structural features of parental input resulted modified. Mediation analyses pointed out that the intervention indirectly enhanced late-talkers’ use of verbal types and tokens through changes in parental use of expansions and amount of talking over reading. As birth status was entered as a covariate in the analysis, these findings can be extended to children with different gestational age. We conclude that the parent-implemented intervention was effective in supporting late-talkers' gains in language development as a cascade result of the improvements in parental contingency and dialogic reading abilities. These promising findings suggest to examine not only children and parental outcomes but also the intervention mechanisms promoting changes in late-talkers’ language development as a clearer view on such process can inform the development of feasible, ecological and effective programs.